Does location matter? A spatial analysis of the factors influencing adoption of cereal-legume intercropping among smallholder farming households in Malawi - Chigwe, Tabitha C. Nindi (International Food Policy Research Institute, 2024)
This study examines the adoption of sustainable agricultural intensification practices— particularly cereal-legume intercropping—by smallholder farming households in Malawi. The focus of the study is on how spatial variation in key factors related to agricultural production and marketing influences farming households’ decision-making processes under risk. Separate analyses are done for six distinct agroecological zones in Malawi to evaluate how resource and market constraints affect farming households’ decisions to employ intercropping practices on their cropland and how the variations in these constraints have differing impacts on adoption of intercropping across different regions. This study provides valuable insights into the complexities of smallholder farming choices in diverse geographic contexts.